2020
DOI: 10.1002/ana.25811
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Alzheimer's Disease Cerebrospinal Fluid Biomarkers in Early Parkinson's Disease

Abstract: Objective We analyzed the longitudinal profile of Alzheimer's disease (AD) cerebrospinal fluid (CSF) biomarkers in early Parkinson's disease (PD) compared with healthy controls (HCs) and tested baseline CSF biomarkers for prediction of clinical decline in PD. Methods Amyloid‐β 1 to 42 (Aβ42), total tau (t‐tau) and phosphorylated tau (p‐tau) at the threonine 181 position were measured using the high‐precision Roche Elecsys electrochemiluminescence immunoassay in all available CSF samples from longitudinally stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
61
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 50 publications
9
61
1
Order By: Relevance
“…However, our CSF samples were taken in much later stages of disease than are currently available in studies like PPMI; the mean duration of the disease was 10.4 (±4.8) years and the longest duration in the sample was 23 years. Commensurate with their increased disease duration, these individuals were older than those in the most recent reports from PPMI (71.6 years vs. 61.4 years in PPMI) 22 . Additionally, among the FOG group here, there was no evidence of substantial executive dysfunction – the average MoCA score was 24.1 (results published separately 12 ).…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…However, our CSF samples were taken in much later stages of disease than are currently available in studies like PPMI; the mean duration of the disease was 10.4 (±4.8) years and the longest duration in the sample was 23 years. Commensurate with their increased disease duration, these individuals were older than those in the most recent reports from PPMI (71.6 years vs. 61.4 years in PPMI) 22 . Additionally, among the FOG group here, there was no evidence of substantial executive dysfunction – the average MoCA score was 24.1 (results published separately 12 ).…”
Section: Discussionmentioning
confidence: 61%
“…One study suggested an association of low baseline levels to worse motor scores and, in particular, postural instability gait disorder (PIGD) sub score 22 Our results suggest that the associations between lower CSF Aβ42 and incident FOG that hold in newly diagnosed PD patients 13 may not generalize to older or more advanced patients. FOG is also associated with cognitive decline, particularly executive dysfunction [7][8][9] which is associated with lower Aβ42.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations